Respuesta :

Answer :

[tex]\bf (x+y)^2(x-y)^2[/tex]

==============

Solving Steps:

===============

[tex]\rightarrow \sf x^4-2x^2y^2+y^4[/tex]

breakdown

[tex]\rightarrow \sf x^4-x^2y^2-x^2y^2+y^4[/tex]

factor common term

[tex]\rightarrow \sf x^2(x^2-y^2)-y^2(x^2-y^2)[/tex]

collect in groups

[tex]\rightarrow \sf (x^2-y^2)(x^2-y^2)[/tex]

apply difference between two square method: x² - y² = (x+ y)(x-y)

[tex]\rightarrow \sf (x+y)(x-y) (x+y)(x-y)[/tex]

simplify

[tex]\rightarrow \sf (x+y)^2(x-y)^2[/tex]

ACCESS MORE